Self-Healing of Precoated AISI 441 for Solid Oxide Fuel Cell Interconnects at Intermediate Temperatures. (30th May 2017) - Berger, Robert; Lundberg, Mats W; Westlinder, Jörgen
Abstract : Sandvik Materials Technology develops nanocoatings for SOFC stainless steel interconnects. The properties of cerium cobalt coated AISI441 (EN 1.4509) have previously been studied extensively. However, the trend in SOFC have been to decrease working temperatures from above 800°C and today commercial systems are sold that operate below 650°C. The lower operating temperature opens up new possibilities in selection of component materials. In this study we have studied precoated AISI 441 used in solid oxide fuel cell interconnects at 650°C. The coating characteristics after different oxidation times were studied by SEM. Also, by using the double trench approach samples with and without pre-oxidizing at 900°C for 5 hours followed by heat treatment at 650°C, were compared.